What are the strategies for prevention of bronchopulmunary dysplasia?: Review [Bronkopulmoner displazi gelişimini önleme stratejileri nelerdir?] - (:unkn) unknown (My University, 2011)
Bronchopulmonary Dysplasia (BPD) is a chronic pulmonary disease of the preterm, especially of those with a gestational age < 32 weeks and with a birth weight < 1000 grams, who had prolonged mechanical ventilation. A variety of strategies to prevent BPD has been developed. Early CPAP and surfactant administration lowers the incidence BPD. When low target values for oxygen saturation are aimed, duration of hospitalization and frequency of BPD decreases. When recommended ventilator parameters and blood gas values are utilised ventilator-induced lung injury is minimized. Early medical treatment of patent ductus arteriosus decreases the frequency of BPD. Nutritonal measures lowers morbidity and duration of hospitalization in preterm babies. Administration of vitamin A to preterm babies decreases mortality rate and frequency of BPD. Effects of postnatal steroids depend on time when steroids applied, duration of administration, total steroid dosage and type of steroid used. Caffein when used in the first 10 days lowers the risk of BPD. Inhaled nitric oxide causes pulmonary vasodilation thus lowers ventilation-induced lung injury. Modern therapies have acute benefits with undetermined longterm effects. More studies are needed to understand the pathogenesis of the disease, for better preventive measures and development of new treatment modalities. Copyright © 2011 by Türkiye Klinikleri.
Keywords: Bronchopulmonary dysplasia; Caffeine; Ductus arteriosus; Nitric oxide; Patent; Pulmonary surfactants; Vitamin a